Do aesthetics dental needs interfere in the quality of life of patients? - Karina Ferreira Rizzardi; Leonardo Caldas Vieira; Thais Manzano Parisotto; Cristiane Franco Pinto (Universidade Estadual de Campinas, 2017)
Aim: The objective was to evaluate oral health-related quality of life (OHRQOL) in patients aging 18 - 60 years, considering oral health, dental aesthetic impact and self-esteem. Methods: The sample comprised 81 patients, regardless gender/ethnicity, seeking for dental aesthetic treatment at University São Francisco, Bragança Paulista-SP. The instruments used to assess the OHRQOL were the questionnaires: 1. Rosenberg Self-Esteem Scale (RSS); 2. Oral Health Impact Profile-14 Brazil (OHIP) and 3. Psychosocial Impact and Aesthetic Dental Questionnaire-Brazil (PIADQ). Data were analyzed by Spearman correlation (α=5%) and descriptive statistics. Results: The older the patient the worse the oral and general health conditions found (p<0.05). Moreover, the age showed significant correlation with OIHP and PIADQ questionnaires scores (p=0.000). The three questionnaires showed moderate positive correlations (p<0.05 r=0.461 - 0.685) among them. In addition, OHIP and QIPED questionnaires correlated with general health and oral health (p<0.05 r=0.230-0.558). Conclusion: It could be concluded that aesthetic dental needs interfere, in fact, in the oral health-related quality of life and in the self-steem of patients seeking for treatment University São Francisco Dental School.